Adaptive Memory: Independent Effects of Survival Processing and Reward Motivation on Memory - Forester, Glen; Kroneisen, Meike; Erdfelder, Edgar; Kamp, Siri-Maria (Frontiers in Human Neuroscience, 2020)
Humans preferentially remember information processed for their survival relevance, a memorial benefit known as the survival processing effect. Memory is also biased towards information associated with the prospect of reward. Given the adaptiveness of these effects, they may depend on similar mechanisms. We tested whether motivation drives both effects, with reward incentives that are known to boost extrinsic motivation and survival processing perhaps stimulating intrinsic motivation. Accordingly, we manipulated survival processing and reward incentive independently during an incidental-encoding task in which participants chose between pairs of words concerning their relevance for a scenario, and examined the effects on encoding event-related potentials (ERP) activity and later performance on a surprise recall test. We hypothesized that if survival processing fosters intrinsic motivation, it should reduce the beneficial effects of extrinsic motivation (reward incentive). In contrast to this prediction, we found that reward incentive and survival processing independently improved memory and that the P300, a measure of lower-level cognitive resource allocation, was increased by reward incentive independent of survival processing. Further, survival processing and reward incentive independently increased the frontal slow wave (FSW), a measure of higher-level elaboration. These findings suggest that while survival processing and reward incentive may both increase encoding elaboration, the memory-enhancing effect of survival processing does not depend on increased intrinsic motivation. Additionally, we replicated a recent finding whereby the survival processing effect generalizes to a choice-based encoding task and further showed that the beneficial effect of choice on memory likely does not interact with either survival processing or reward.